Elian granules alleviate precancerous lesions of gastric cancer in rats by suppressing M2-type polarization of tumor-associated macrophages through NF-κB signaling pathway - Zhirong Yi; Qingling Jia; Yujiao Wang; Yuqin Zhang; Tianyi Xie; Jianghong Ling (BMC Complementary Medicine and Therapies, 2023)
Abstract Background Precancerous lesions of gastric cancer (PLGC) refer to a kind of histopathological changes in the gastric mucosa that can progress to gastric cancer. Elian granules (ELG), a Chinese medicinal prescription, have achieved satisfactory results in the treatment of PLGC. However, the exact mechanism underlying the therapeutic effect of ELG remains unclear. Here, this study aims to explore the mechanism of ELG alleviating PLGC in rats. Methods The chemical ingredients of ELG were analyzed using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS). Specific Pathogen Free SD rats were randomly assigned to 3 groups: the control, model, and ELG groups. The 1-Methyl-3-nitro-1-nitrosoguanidine (MNNG) integrated modeling method was adopted to construct the PLGC rat model in groups except for the control group. Meanwhile, normal saline was used as an intervention for the control and model groups, and ELG aqueous solution for the ELG group, lasting 40 weeks. Subsequently, the stomach of rats was harvested for further analysis. Hematoxylin-eosin staining of the gastric tissue was conducted to assess the pathological changes. Immunofluorescence was carried out for the expression of CD68, and CD206 proteins. Real-time quantitative PCR combined with Western blot was conducted to analyze the expression of arginase-1(Arg-1), inducible nitric oxide synthase (iNOS), p65, p-p65, nuclear factor inhibitor protein-α (IκBα), and p-IκBα in gastric antrum tissue. Results Five chemical ingredients including Curcumol, Curzerenone, Berberine, Ferulic Acid, and 2-Hydroxy-3-Methylanthraquine were identified in ELG. The gastric mucosal glands of rats treated with ELG were orderly arranged, with no intestinal metaplasia and no dysplasia. Furthermore, ELG decreased the percentage of M2-type TAMs marked with CD68 and CD206 proteins, and the ratio of Arg-1 to iNOS in the gastric antrum tissue of rats with PLGC. In addition, ELG could also down-regulate the protein and mRNA expression of p-p65, p65, and p-IκBα, but up-regulate the expression of IκBα mRNA in rats with PLGC. Conclusions The results showed that ELG attenuates PLGC in rats by suppressing the M2-type polarization of tumor-associated macrophages (TAMs) through NF-κB signaling pathway.